Severely altered guanidino compound levels, disturbed body weight homeostasis and impaired fertility in a mouse model of guanidinoacetate N-methyltransferase (GAMT) deficiency. - Schmidt, A; Marescau, B; Boehm, E; Renema, W; Peco, R; Das, A; Steinfeld, R; Chan, S; Wallis, J; Davidoff, M; Ullrich, K; Waldschütz, R; et al. (2004)
We generated a knockout mouse model for guanidinoacetate N-methyltransferase (GAMT) deficiency (MIM 601240), the first discovered human creatine deficiency syndrome, by gene targeting in embryonic stem cells. Disruption of the open reading frame of the murine GAMT gene in the first exon resulted in the elimination of 210 of the 237 amino acids present in mGAMT. The creation of an mGAMT null allele was verified at the genetic, RNA and protein levels. GAMT knockout mice have markedly increased guanidinoacetate (GAA) and reduced creatine and creatinine levels in brain, serum and urine, which are key findings in human GAMT patients. In vivo (31)P magnetic resonance spectroscopy showed high levels of PGAA and reduced levels of creatine phosphate in heart, skeletal muscle and brain. These biochemical alterations were comparable to those found in human GAMT patients and can be attributed to the very similar GAMT expression patterns found by us in human and mouse tissues. We provide evidence that GAMT deficiency in mice causes biochemical adaptations in brain and skeletal muscle. It is associated with increased neonatal mortality, muscular hypotonia, decreased male fertility and a non-leptin-mediated life-long reduction in body weight due to reduced body fat mass. Therefore, GAMT knockout mice are a valuable creatine deficiency model for studying the effects of high-energy phosphate depletion in brain, heart, skeletal muscle and other organs.